2018
DOI: 10.1002/ijc.31399
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and outcome of adult‐onset neuroblastoma

Abstract: Adult-onset neuroblastoma is rare and little is known about its biology and clinical course. There is no established therapy for adult-onset neuroblastoma. Anti-GD2 immunotherapy is now standard therapy in children with high-risk neuroblastoma; however, its use has not been reported in adults. Forty-four adults (18-71 years old) diagnosed with neuroblastoma between 1979 and 2015 were treated at Memorial Sloan Kettering Cancer Center. Five, 1, 5 and 33 patients had INSS stage 1, 2, 3 and 4 diseases, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
58
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 49 publications
5
58
1
7
Order By: Relevance
“…Only a few studies have looked at ATRX mutations in adult‐onset neuroblastoma. By sequencing, mutations were detected in 19/32 cases altogether (59%) in keeping with the concept that mutations in ATRX are most frequent in older patients. Only one study carried out ALT assessment by FISH and found 3/3 cases with ATRX mutations also showed ALT by FISH .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Only a few studies have looked at ATRX mutations in adult‐onset neuroblastoma. By sequencing, mutations were detected in 19/32 cases altogether (59%) in keeping with the concept that mutations in ATRX are most frequent in older patients. Only one study carried out ALT assessment by FISH and found 3/3 cases with ATRX mutations also showed ALT by FISH .…”
Section: Discussionsupporting
confidence: 78%
“…The best documented difference is the increased frequency of ATRX mutations in adult cases . Such patients have protracted courses and do not respond as well to standard chemotherapy . The finding that 80% of our cases tested showed genetic changes in keeping with telomere maintenance provides a molecular confirmation of the high‐risk biology of adult neuroblastoma.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Так, в группе пациентов старше 5 лет на момент постановки диагноза крайне редко встречается амплификация MYCN, но сравнительно чаще наблюдается первичная резистентность. Учитывая биологическую гетерогенность заболевания [17], различное клиническое течение и ответ на терапию в разных возрастных группах, пациенты более старшего возраста могут требовать дифференцированного подхода к терапии [18].…”
Section: Discussionunclassified
“…The treatment for childhood neuroblastoma is well established and involves a multimodality approach consisting mainly of chemotherapy, radiotherapy and surgery; however, there is no well-established treatment algorithm for adults. New studies have suggested that treatment with anti-GD2 immunotherapy may improve survival but larger randomised controlled studies are required in adults 7…”
Section: Discussionmentioning
confidence: 99%